Análisis de la vulneración del derecho a la educación, a la salud y una vida digna de niños dentro del contexto de causas y vías de solución - Salas Ballesteros, Joseelyn Coralia (2025)
This research study addresses the analysis of the violation of the fundamental rights of children and adolescents in Ecuador: the right to education, the right to health, and the right to a dignified life. The main objective is to identify the primary causes behind these violations and to propose possible solutions from a comprehensive, rights-based perspective. The study was conducted using a qualitative methodology, through interviews with several families living in vulnerable conditions, as well as with professionals experienced in the legal and child protection fields, including lawyers and judges specializing in family, childhood, and adolescence. In addition, documentary analysis was used to theoretically support the findings. Among the main factors that contribute to the violation of these rights are poverty, social exclusion, domestic violence, school dropout, lack of access to basic services, chronic child malnutrition, and institutional weakness in effectively guaranteeing child protection. Based on these findings, various solutions are proposed, including: strengthening regulatory institutions, implementing public policies with a rights-based and territorial approach, promoting mediation as both a preventive and conflict-resolution mechanism, and encouraging shared responsibility among the State, the family, and the community.